Copy Number Alterations in Hepatoblastoma: Literature Review and a Brazilian Cohort Analysis Highlight New Biological Pathways - Barros, Juliana Sobral; Aguiar, Talita Ferreira Marques; Costa, Silvia Souza; Rivas, Maria Prates; Cypriano, Monica; Toledo, Silvia Regina Caminada; Novak, Estela Maria; Odone, Vicente; Cristofani, Lilian Maria; Carraro, Dirce Maria; Werneck da Cunha, Isabela; Costa, Cecília Maria Lima; et al. (Frontiers in Oncology, 2021)
Hepatoblastoma (HB) is a rare embryonal tumor, although it is the most common pediatric liver cancer. The aim of this study was to provide an accurate cytogenomic profile for this type of cancer, which information in cancer databases is lacking. The copy number alteration (CNA) profile of a Brazilian cohort of 26 HBs was obtained by array-CGH. The most frequent CNA were 1q, 2/2q, 8/8q and 20 for gains and 1p and 4q for losses. Analysis identified six hot-spots chromosome regions most frequently affected in the cohort: 1q31.3q42.3, 2q23.3q37.3, and 20p13p11.1 gains, besides a 5,3 Mb amplification at 2q24.2q24.3, and losses at 1p36.33p35.1, 4p14 and 4q21.22q25. An in-silico analysis using the genes mapped in these six regions revealed several enriched biological pathways such as ERK Signaling, MicroRNAs in Cancer and the PI3K-Akt Signaling, in addition to the WNT Signaling pathway. The analyzed gene set was found to be associated with neoplasms, abnormalities of metabolism/homeostasis and liver morphology, as well as abnormal embryonic development and abnormal cytokine secretion. In addition, we performed an extensive literature review of cytogenetic studies on hepatoblastoma tumors disclosing the most common copy number alterations in HB being gains in 1q, 2/2q, 8/8q, and 20; and losses in 1p and 4q. In conclusion, we have provided an extensive characterization of the spectrum of chromosomal alterations reported for HB and have identified specific genomic regions frequently altered in a Brazilian HB cohort, pointing to new biological pathways, part of them not linked to the canonical WNT signaling pathway. Further investigation is required to evaluate if disturbances in theses pathways can lead to HB tumorigenesis.